COLLAPSE OF ARRUDA STREET LOCATED NEAR THE BAIXA FUNDA STREAM IN ARAGUAÍNA-TO - Aires, Denia Carla Dias Costa; da Silva, Marivaldo Cavalcante (Seven Editora, 2025)
This article is a study of the landslides that occurred on a stretch of Rua da Arruda, part of the widening of Avenida Filadélfia, TO 2022 in Araguaína-TO. According to Alencar and Vasconcelos (2011, p. 145), "As a strategic city for the state of Tocantins, Araguaína presents serious problems regarding urban planning." Therefore, the general objective of this work is to address these landslides, show the environmental problems that occur around them, but specifically in the Baixa Funda stream, as well as show the changes that occurred in the space from 2014 to 2025. The methodology used was a bibliographic survey of subjects related to the topic, on sites such as SciELO, Google Scholar, among others. Field research was also carried out, using Figuregraphs and interviews with some residents who live near this stretch of the road. DOI: https://doi.org/10.56238/sevened2025.029-042